Electrostatic Ignition Hazards Associated with Dissipative Dust Filters. (September 2015) - Glor, M; Forestier, S; Meier, P
Abstract: In present guidelines and codes of practice it is strongly recommended to use dissipative filter media in dust separators, if the minimum ignition energy of the powder is below 3 mJ and/or a hybrid mixture may be present. Despite being in compliance with this rule and despite the filter media passed the relevant tests, burnt product was found in a dust separator of pharmaceutical production. Extensive investigations have shown that the demands made in the present standards on dissipative filter clothes are not sufficient to prevent ignition of deposited powder and ignition of an explosive atmosphere. Proposals for additional tests and requirements are presented in the paper.